2016
DOI: 10.1071/fp15265
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing salt tolerance in quinoa by halotolerant bacterial inoculation

Abstract: Quinoa is a facultative halophytic seed crop of increasing interest worldwide. Its performance declines under high salinity but can be improved by using halotolerant plant growth-promoting bacteria (PGPB) containing multi-traits, i.e. ACC-deaminase activity, exopolysaccharide secretion and auxin production. This study focussed on improving the productivity of quinoa through the use of six plant growth-promoting bacterial strains (both endophytic and rhizosphere). These were screened by conducting osmoadaptatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 47 publications
9
57
0
Order By: Relevance
“…Growth and yield decreased significantly under saline irrigation in the present study (Figure ), also demonstrated previously by Yang et al. (). However, priming with saponin leads to positive effects both under saline irrigation and non‐saline irrigation, most pronounced after the application of 15% and 25% saponin.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Growth and yield decreased significantly under saline irrigation in the present study (Figure ), also demonstrated previously by Yang et al. (). However, priming with saponin leads to positive effects both under saline irrigation and non‐saline irrigation, most pronounced after the application of 15% and 25% saponin.…”
Section: Discussionsupporting
confidence: 92%
“…Leaf CCI content was increased under salinity condition (Figure ), which might be due to enhanced nitrogen‐containing compounds, and similar findings were reported in our previous study on quinoa (Yang et al., ). However, only application of saponins at 15% as a priming agent could significantly enhance A n and g s under salinity.…”
Section: Discussionsupporting
confidence: 88%
“…The salinity‐induced ionic imbalance and oxidative damages resulted in a decline of photosynthesis, which eventually lead to significant reduction in plant height, panicle length and grain yield of quinoa (Yang et al , Iqbal et al , Yang et al ). PBZ application improved grain yield and its contributing attributes under saline conditions (Table ), which can be attributed to an appropriate functioning of the plant's photosystems under salinity.…”
Section: Discussionmentioning
confidence: 99%
“…Quinoa also provides a highly nutritious food source that can be cultivated on marginal environments, which is not currently feasible for other major crops. Quinoa can achieve optimal growth and biomass between 100 and 200 mM (10, 20 dS m −1 ) of salinity (Jacobsen et al , Hariadi et al , Iqbal et al ), and 400 mM salinity causes significant reduction in growth and yield (Hariadi et al , Yang et al , Waqas et al , Yang et al ). However, the salt tolerance potential of quinoa greatly differs among genotypes (Schmockel et al ).…”
Section: Introductionmentioning
confidence: 99%
“…MN54 was previously evaluated for enhancing growth and physiological attributes of Quinoa under normal and salt-stressed conditions (Yang et al 2016). The inoculum of selected bacterial strain MN54 was prepared using 10% Tryptic Soy Broth in 1000 mL Erlenmeyer flask incubated in a shaking incubator (Firstek Scientific, Tokyo, Japan) at 100 r.min -1 for 72 h at 28±1°C.…”
Section: Culture Preparation Of Bacillus Sp Mn54 and Trichoderma Spmentioning
confidence: 99%